Multinational Association of Supportive Care in Cancer (MASCC) clinical practice guidelines for the prevention and management of acute radiation dermatitis: international Delphi consensus-based recommendations. Issue 4 (April 2023) - Behroozian, Tara; Bonomo, Pierluigi; Patel, Partha; Kanee, Lauren; Finkelstein, Samuel; van den Hurk, Corina; Chow, Edward; Wolf, Julie Ryan; Behroozian, Tara; Bonomo, Pierluigi; Patel, Partha; et al.
Summary: Acute radiation dermatitis is a frequent adverse effect of radiotherapy, but standardisation of care for acute radiation dermatitis is lacking. Due to the conflicting evidence and variability in current guidelines, a four-round Delphi consensus process was used to compile opinions of 42 international experts on care for people with acute radiation dermatitis on the basis of the evidence in existing medical literature. Interventions for acute radiation dermatitis prevention or management that reached at least 75% consensus were recommended for clinical use. Six interventions could be recommended for the prevention of acute radiation dermatitis: photobiomodulation therapy and Mepitel film in people with breast cancer, Hydrofilm, mometasone, betamethasone, and olive oil. Mepilex Lite dressings were recommended for the management of acute radiation dermatitis. Most interventions were not recommended due to insufficient evidence, conflicting evidence, or lack of consensus to support use, suggesting a need for further research. Clinicians can consider implementing recommended interventions in their practice to prevent and manage acute radiation dermatitis until additional evidence becomes available.